Inclusion of vegetable oils in diets of broiler chicken raised in hot weather and effects on antioxidant capacity, lipid components in the blood and immune responses - Rafei-Tari, Ali (2021)
The aim of this study was to assess the effects of vegetable oils on the antioxidant capacity, blood lipid components and immune responses in chickens raised in hot climate. In a completely randomized design, 300 chicks were assigned to four treatments and five replicates with 15 chicks per each. The highest concentration of malondialdehyde was found in broilers fed palm oil (p < 0.05). Chickens fed corn oil had the lowest and those fed flaxseed oil had the highest antioxidant enzymes activities (p < 0.05). The highest hepatic Alanine-transferase and Aspartate-transferase was found in chickens fed corn oil and the lowest levels in those received flaxseed and olive oils (p < 0.05). The highest hypersensitivity was in chickens fed palm oil and the lowest was for olive oil. The highest antibody titer against sheep red blood cells was found in chickens fed flaxseed oil and the lowest titer was for those received palm oil (p < 0.05). The highest triglyceride, cholesterol and very low density lipoprotein and the lowest high density lipoprotein was found in chickens fed palm oil and vice versa for flaxseed and olive oils. Olive and flaxseed oils had beneficial effects on antioxidant activity and lipid attributes and palm oil had detrimental effects on these parameters that related to the poultry health.